Socialization of Yellowtail Fusilier (Caesio cunning) Processing to The Community of Langagedha 1 Village, Bajawa District, Bajawa Regency - Kristiana Lali Kadju; Maria Daflora Timang (CV. Dharma Samakta Edukhatulistiwa, 2026)
Yellowtail fusilier, or Caesio cuning, is a type of marine fish commonly found in Indonesian waters. This fish is known for its distinctive bright yellow tail fin, bluish upper body, and white to pink underside and belly. Fish meatballs are typically prepared using ingredients such as fish meat, wheat flour, starch, chicken eggs, and several other spices. Furthermore, because meatballs are processed product with a high nutritional and water content, they have a relatively short shelf life, lasting only 12 hours to 1 day at room temperature. The purpose of this community service is to educate the community of Langagedha 1 Village on how to manage fish products. This is done to provide knowledge to the community to innovate and implement more modern fish management. Local villagers also have the opportunity to become entrepreneurs using fish as the main ingredient to increase their income. The methods used include discussion, socialization, and hands-on practice. The results of this activity showed that the community of Langagedha 1 Village was able to participate well and was very enthusiastic, thus mastering the process of making Yellowtail fusilier meatballs. Processing Yellowtail fusilier into meatballs can be a viable option, motivating people to start businesses. Yellowtail fusilier meatballs are easy to make because the raw materials are readily available and inexpensive.